Keefektifan Formula Pseudomonas fluorescens Untuk Mengendalikan Penyakit Layu Bakteri dan Meningkatkan Pertumbuhan Tanaman Nilam - Nasrun Nasrun; Nurmansyah Nurmansyah (Jurnal Fitopatologi Indonesia, 2016)
Bacterial wilt disease (Rasltonia solanacearum) is an important constraint for patchouli plant. Formulated Pseudomonas fluorescens Pf19 could induce patchouli plant resistance against R. solanacearum. The aims of the present study were to find the optimal dose and application interval of formulated P. fluorescens Pf19 in order to control R. solanacearum effectively and efficiently, as well as promoting the growth and productivity of the patchouli plant. The results of effectivity test of doses (75 g L-1 and 100 g L-1) and application time intervals (every 30; 60; 90 and 120 days) showed that formulation of P. fluorescens Pf19 controlled bacterial wilt disease and increased patchouli  plant growth and production on patchouli plant in field. Doses of 100 g L-1 and application time of every 30 and 60 days had highest activity and effectivity to control bacterial wilt diseases and increase plant growth and production of patchouli plant. Incubation period was 88.0–93.5 days after planting, and disease intensity was 16.50–24.12%. The same treatments may increase the growth of patchouli plant, i.e. plant height were 59.0–68.5 cm, total number of leaves were 417.5–510.0 leaves per plant, wet weight of leaves were 234.55–263.45 g per plot and dry weight of leaves were 25.32–29.28 g per plot.